Copper-Adapted Suillus luteus, a Symbiotic Solution for Pines Colonizing Cu Mine Spoils - Adriaensen, K. (American Society for Microbiology, 2005)
Natural populations thriving in heavy-metal-contaminated ecosystems are often subjected to selective pressures for increased resistance to toxic metals. In the present study we describe a population of the ectomycorrhizal fungus Suillus luteus that colonized a toxic Cu mine spoil in Norway. We hypothesized that this population had developed adaptive Cu tolerance and was able to protect pine trees against Cu toxicity. We also tested for the existence of cotolerance to Cu and Zn in S. luteus. Isolates from Cu-polluted, Zn-polluted, and nonpolluted sites were grown in vitro on Cu- or Zn-supplemented medium. The Cu mine isolates exhibited high Cu tolerance, whereas the Zn-tolerant isolates were shown to be Cu sensitive, and vice versa. This indicates the evolution of metal-specific tolerance mechanisms is strongly triggered by the pollution in the local environment. Cotolerance does not occur in the S. luteus isolates studied. In a dose-response experiment, the Cu sensitivity of nonmycorrhizal Pinus sylvestris seedlings was compared to the sensitivity of mycorrhizal seedlings colonized either by a Cu-sensitive or Cu-tolerant S. luteus isolate. In nonmycorrhizal plants and plants colonized by the Cu-sensitive isolate, root growth and nutrient uptake were strongly inhibited under Cu stress conditions. In contrast, plants colonized by the Cu-tolerant isolate were hardly affected. The Cu-adapted S. luteus isolate provided excellent insurance against Cu toxicity in pine seedlings exposed to elevated Cu levels. Such a metal-adapted Suillus-Pinus combination might be suitable for large-scale land reclamation at phytotoxic metalliferous and industrial sites.